2017
DOI: 10.1080/21645515.2017.1340138
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DQB1*06 and breadth of Nef core region-specific T-cell response are associated with slow disease progression in antiretroviral therapy-naive Chinese HIV-1 subtype B patients

Abstract: Vaccines still are an important way to prevent and treat acquired immunodeficiency syndrome (AIDS). For developing an effective T cell-based AIDS vaccine, it is critical to define the human leukocyte antigen (HLA) type and epitope that elicit the most potent responses. This study involved 29 antiretroviral therapy-naive and chronic human immunodeficiency virus (HIV)-1 subtype B-infected individuals. A polymerase chain reaction-sequence-specific primer was used to detect the HLA typing, and the enzyme-linked im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…[ 30 ] HLA-DQB106 , a variant allele of the HLA-DQB1 gene, has been found to play a protective role against HIV-1 disease progression and the targeting of T cells by specific Nef epitopes, thereby contributing to the suppression of HIV-1 replication. [ 31 ] Individuals with the strongest HIV-specific CD4 + T-cell responses commonly carry HLA class II gene-specific alleles, such as HLA-DRB113 and/or HLA-DQB106 , which have previously been associated with non-progressive HIV infection phenotypes. [ 32 ] This indicates that HLA-DQB106 plays an important and positive role in the regulation of the immune response to HIV-1 infection.…”
Section: Discussionmentioning
confidence: 99%
“…[ 30 ] HLA-DQB106 , a variant allele of the HLA-DQB1 gene, has been found to play a protective role against HIV-1 disease progression and the targeting of T cells by specific Nef epitopes, thereby contributing to the suppression of HIV-1 replication. [ 31 ] Individuals with the strongest HIV-specific CD4 + T-cell responses commonly carry HLA class II gene-specific alleles, such as HLA-DRB113 and/or HLA-DQB106 , which have previously been associated with non-progressive HIV infection phenotypes. [ 32 ] This indicates that HLA-DQB106 plays an important and positive role in the regulation of the immune response to HIV-1 infection.…”
Section: Discussionmentioning
confidence: 99%
“…A Chinese study also found that HLA DQB1*06 had protective effect on the evolution of HIV infection and T-cell targeting of specific HIV Nef epitopes. This study even proposes the consideration of the presence of HLA DQB1*06 in the production of the anti-HIV vaccine, given the role of this allele in the promotion of specific anti-HIV lymphocyte immune response [ 24 ]. Regarding Epstein Barr Virus (EBV) infection, it was found that people homozygous for HLA DQB1*06 were more likely to be EBV seronegative than other DQB1 combinations [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several polymorphisms in the HLA loci, especially HLA-II, are related to HBV infection susceptibility or spontaneous HBV clearance [610]. Furthermore, HLA-DQB1 gene polymorphisms are associated with the progression of human immunodeficiency virus infection [11], HCV infection susceptibility and spontaneous clearance [12], coronary artery disease [13], rheumatoid arthritis [14], and other diseases.…”
Section: Introductionmentioning
confidence: 99%